Confirmación de Argas neghmei (Ixodida: Argasidae) en Perú y reporte del carpintero andino (Colaptes rupicola) como nuevo hospedero - Gomez-Puerta, Luis A. (2020)
This report describes the finding of soft ticks (Ixodida, Argasidae) parasitizing two Andean flickers (Colaptes rupicola) from the Nuñoa district, Melgar province in Puno, Peru (14°31'11.77"S; 70°32'15.95''W; elevation 3967 m). A total of 29 larval ticks were collected directly from the birds and morphologically identified as Argas neghmei. Diagnosis was based on the larval morphology and confirmed by molecular analysis of the tick mitochondrial 16S rRNA gene. A sequence of 363 base pair of this gene showed to be 100% identical with sequences of A. neghmei from Argentina and Chile (GenBank: FJ853598 and DQ295781). This finding confirms the presence of A. neghmei in Peru and adds the Andean flicker as a new host for this species.